Diagnostic Utility of D‐Dimer Concentrations in Dogs with Pulmonary Embolism. (28th August 2013) - Epstein, S.E.; Hopper, K.; Mellema, M.S.; Johnson, L.R.
<x xml:space="preserve">Abstract</x> Background Pulmonary embolism (PE) is a complication of systemic disease in dogs. Antemortem diagnosis is challenging because of the lack of a confirmatory test. Objectives To retrospectively determine the diagnostic utility of D‐dimer concentrations in dogs with necropsy‐confirmed PE. Animals Ten dogs with PE confirmed at necropsy that had D‐dimer concentrations measured and 10 control dogs with D‐dimer concentrations available that lacked PE on necropsy. Methods The computerized medical record database was searched for dogs with necropsy‐confirmed PE that had D‐dimer concentrations measured at that visit. An age‐, sex‐, and breed‐matched control group was identified. Signalment, location of PE, and coagulation profiles were collected. Sensitivity, specificity, negative predictive value (NPV), and positive predictive value (PPV) were calculated using a D‐dimer concentration of 250 ng/mL. Results Coagulation profiles were not different between dogs with and without PE. Using 250 ng/mL as a cut‐off D‐dimer concentration, the sensitivity and specificity were 80 and 30%, respectively, for the diagnosis of PE. The NPV and PPV were 60 and 53.0%, respectively. D‐dimer concentration <103 ng/mL had 100% sensitivity for ruling out PE and no value was 100% specific. Conclusions and Clinical Importance D‐dimer concentrations <250 ng/mL have a high sensitivity for the absence of PE, but PE still can occur in dogs with a normal D‐dimer concentration. Increased D‐dimer concentrations are not specific for PE.